2015
DOI: 10.1371/journal.pone.0117970
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Local Lamellipodia in Endothelial Barrier Function

Abstract: Recently we observed that endothelial cells cultured in tightly confluent monolayers display frequent local lamellipodia, and that thrombin, an agent that increases endothelial permeability, reduces lamellipodia protrusions. This led us to test the hypothesis that local lamellipodia contribute to endothelial barrier function. Movements of subcellular structures containing GFP-actin or VE-cadherin-GFP expressed in endothelial cells were recorded using time-lapse microscopy. Transendothelial electrical resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
114
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(123 citation statements)
references
References 70 publications
6
114
3
Order By: Relevance
“…Together with these findings, the BBB tight junction proteins including ZO-1, occludin, and claudin 5 in brain microvessels were reduced ( Figure 2F; supplemental Figure 2E-G), and collagen IV 1 basement membrane coverage was 54% less in Adamts13 2/2 mice ( Figure 2G). In agreement with this result, actin stress fiber formation, which is associated with irregular endothelial junctions and elevated endothelial permeability, 35 was increased by 2.2-fold in Adamts13 2/2 mice ( Figure 2H). In addition, Adamts13 …”
Section: Adamts13 Deficiency Disrupts Vascular Integrity and Exacerbasupporting
confidence: 85%
“…Together with these findings, the BBB tight junction proteins including ZO-1, occludin, and claudin 5 in brain microvessels were reduced ( Figure 2F; supplemental Figure 2E-G), and collagen IV 1 basement membrane coverage was 54% less in Adamts13 2/2 mice ( Figure 2G). In agreement with this result, actin stress fiber formation, which is associated with irregular endothelial junctions and elevated endothelial permeability, 35 was increased by 2.2-fold in Adamts13 2/2 mice ( Figure 2H). In addition, Adamts13 …”
Section: Adamts13 Deficiency Disrupts Vascular Integrity and Exacerbasupporting
confidence: 85%
“…As alternatives, we investigated Rac1 and Cdc42, 2 other key Rho family small GTPases that contribute to the control of endothelial barrier function 22, 24, 77, 78, 79. Thrombin caused a rapid, significant decrease in Rac1‐GTP in agreement with several previous reports 17, 78, 80, 81. However, thrombin did not activate Cdc42 in HUVEC, in contrast to one previous report that described a delayed activation of Cdc42 in immortalized human dermal microvascular endothelial cells 71.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, coordinated, cyclic activity of Rac1 and RhoA are known to control the protrusion and withdrawal of cell protrusions 83. Recently, we reported that treatment of endothelial cells with either thrombin or a selective inhibitor of Rac1 can decrease the protrusion frequency of small, local lamellipodia in conjunction with disruption of the endothelial barrier 17. These protrusions, also termed junctional‐associated intermittent lamellipodia by other investigators,84, 85 are also disrupted by histamine and appear to control rapid changes in permeability by altering the overlap of adjacent endothelial cells 18.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations